2015
DOI: 10.5901/mjss.2015.v6n4p481
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Small and Medium Enterprises through Entrepreneurial Orientation and Strategic Improvisation

Abstract: The purpose of this research is to establish the relationships between entrepreneurial orientation (EO), strategic improvisation and performance of small-medium enterprises (SMEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…The items originated from the work of Miner (1998a, 1998b), Tierney et al (1999), Unger and Kernan (1983) and has a Cronbach's alpha of 0.91. The study operationalized SI as the best strategy to cope with flexibility and provide the organization with capabilities to adapt to changing environmental demands rapidly and effortlessly (Bakar et al, 2015b). In terms of OC, the popular Wallach (1983) items of 24 were used.…”
Section: Role Of Organizational Culturementioning
confidence: 99%
See 1 more Smart Citation
“…The items originated from the work of Miner (1998a, 1998b), Tierney et al (1999), Unger and Kernan (1983) and has a Cronbach's alpha of 0.91. The study operationalized SI as the best strategy to cope with flexibility and provide the organization with capabilities to adapt to changing environmental demands rapidly and effortlessly (Bakar et al, 2015b). In terms of OC, the popular Wallach (1983) items of 24 were used.…”
Section: Role Of Organizational Culturementioning
confidence: 99%
“…The concept of SI is an emerging field of study in the management science that deals with providing solutions on how organizations adapt to dynamism of today's environment (Bakar et al, 2015b;Hadida and Tarvainen, 2014). Besides, strict adherence to strategic planning has been identified as a hindrance to creativity, flexibility and the development of an appropriate plan for the organization (Slotegraaf and Dickson, 2004).…”
Section: Strategic Improvisation and Organizational Performancementioning
confidence: 99%
“…Research has shown that one of the key characteristics of entrepreneurs that allows them to perform effectively in such a dynamic and unpredictable business condition is improvisational behavior (Hmieleski and Corbett, 2008;Adomako et al, 2018;Hmieleski et al, 2013). Improvisational behavior is conceptualized as spontaneous action guided by intuition, produced or carried out in the spur of the moment instead of going through intentional thought and evaluation processes (Bakar et al, 2015;Baker and Miner, 2003;Bingham, 2009;Vera et al, 2016). Literature in the area of entrepreneurship shows that improvisational behavior has become even more imperative due to the increase in the complexity and uncertainties of the business environment, coupling with the higher degree of competition and resource scarcity in the present business landscape (Duxbury, 2014;Smith and Blundel, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Under the context of current study, it is defined as a leader's ability to perceive unforeseen situations and improvise efficiently or effectively to solve a problem. In essence, SI is implementation of planning and processes resulting the emergent behavior of an organization (Bakar, Mahmood, & Ismail, 2015). SI is implemented in real time scenarios and situations which involve a great degree of innovation and spontaneity.…”
Section: Leaders' Strategic Improvisationmentioning
confidence: 99%